Novel Tool to Monitor Adherence to Oral Oncolytics: A Pilot Study. (2021) - Sun, Wendy; Reeve, Rebecca; Ouellette, Timothy; Stutsky, Martha; De Jesus, Rachel; Huffer, Michael J.; Mougalian, Sarah S.
Abstract : PURPOSE: Nonadherence is a significant issue in cancer care, especially as more oral therapies become available. Measuring and optimizing adherence to such therapies is challenging. In this study, we tested a novel technology that records real-time medication-taking behavior from a smart prescription bottle and can communicate with patients via text message to intervene in cases of nonadherence. METHODS: We conducted a 28-patient pilot study to assess the feasibility of this technology in measuring and improving adherence in patients taking capecitabine, an oral chemotherapy agent with a complex, cyclical regimen. The study had a preintervention stage, during which patients were monitored, and an intervention stage, during which the text messaging intervention was enabled. RESULTS: During preintervention, patients had an average self-adherence of 89%, and during post intervention, they had an average adherence of 90%. We defined three categories of patients by change in adherence: category 1 (> 8%), category 2 (−8% to 8%), and category 3 (< −8%). Patients in category 1 tended to live in regions with lower average household income (mean = 58, 937 in US dollars [USD]) than those in category 2 (mean = 77, 482 USD) and category 3 (mean = 90, 972 USD). Of poststudy survey respondents, most indicated that they would want to continue using this technology and that they would recommend it to others. CONCLUSION: This novel technology is able to monitor, measure, and intervene for patients taking capecitabine in real time. Adherence overall was high, and some patients appeared to benefit more from text-message interventions. Future work should focus on patients deemed high risk for nonadherence.